Pengaruh Komunikasi Pemasaran, Kualitas Pelayanan, Dan Kepuasan Konsumen Terhadap Volume Penjualan Pada UD. Sumber Mulya Desa Pancor Kabupaten Sumenep - Fasahri, Nuril Ramadhan; Basalamah, Muhammad Ridwan; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The aim of this research is to determine and analyze the influence of marketing communications, service quality and consumer satisfaction on sales volume at UD. Sumber Mulya Pancor Village, Sumenep Regency. The population in the study were UD customers. Sumber Mulya Pancor Village, Sumenep Regency. The approach method uses a non-probability sampling technique, namely purposive sampling, which is a sample collection technique based on certain criteria using a questionnaire distributed to 100 respondents and using the SPSS analysis tool. The research results show that partially service quality and customer satisfaction have a significant effect on sales volume, while marketing communication does not have a significant effect on sales volume at UD. Sumber Mulya Pancor Village, Sumenep Regency. Keywords: Marketing Communications, Service Quality, Consumer Satisfaction, Sales Volume